Culture in its holistic and differential aspect, in anthropology and educational studies - Drozdowicz, Jarema (Kultura-Społeczeństwo-Edukacja, 2019)
In the present day, culture is a term which due to its complex nature, raises many theoretical and methodological questions. It is being perceived as something described more in plural terms rather than as a whole and a universal pattern, despite the impact made on the debate by the globalisation discourse. Therefore, it is presently an object of study in many academic disciplines. However, the discipline, which shows the most significant interest in the scientific investigation of culture, is anthropology. This paper examines the key issues in the understanding of culture within anthropology and its relation to pedagogy. The latter issue is being raised in order to highlight a relatively new anthropological subdiscipline, i.e. anthropology of education as a research perspective which could deliver certain answers to the problem of cultural diversity, multiculturalism, and multicultural education.